SEMIOTIC STUDY ON “TUGU SI RAJA BATAK” IN SAMOSIR ISLAND NORTH SUMATERA - TATAP HASRANI SINAGA; ZAINUDDIN ZAINUDDIN; ANNA RIANA SURYANTI TAMBUNAN (LINGUISTICA, 2020)
The objectives of this study were to find out signs, the realization of signs in to denotative and connotative meanings, and the reasons for signs realization on Tugu Si Raja Batak in Sarimarrihit Village, Sianjur Mula-Mula sub-district, Samosir Regency. The study was conducted using a qualitative approach. The data of this study were taken from Tugu Si Raja Batak. The data of the study were statues and pictures on Tugu Si Raja Batak. The data analysis was taken by observing, interviewing, and then analyzed the data based on the theory proposed by Roland Barthes. The findings indicated that there were twenty-two signs on Tugu Si Raja Batak in four forms, namely human ornaments, animal ornaments, plant ornaments, and carving. The signs of human ornaments were the Si Raja Batak means descendants with different clans and some servants for different work. The signs of animal ornaments made to show that Si Raja Batak and his descendants used the animals around him as transportations. Then, the plant ornaments they were Lime (Pangir) and Banyan tree (Jajabi) appear because the Batak people are famous for traditional medicine that uses plants such as Lime (Pangir) and betel as medicine for sick people, possessed people, and also for offerings to their ancestors. Furthermore, in the Tugu Si Raja Batak, carvings made because the Si Raja Batak seat requires beautiful decoration and their culture to respect the kings